Analysis of Placental Profile in Pregnancy with Hypertension and Its Relationship with the Condition of the Newborn - Eftyaningrum Dwi Wahyu Astutik; Endah Purwanti Handayani; Harlinda Widia Putri; Pranita Kartika Candra Nurhijraheni (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension in pregnancy (HDK) is one of the main complications that contribute to maternal and infant morbidity and mortality. This study aims to analyze the placental profile in pregnancies with hypertension and its relationship with the condition of the newborn. This study used an observational analytical design with a case-control approach. The sample consisted of 60 respondents consisting of 30 mothers with HDK (case group) and 30 mothers without hypertension (control group), selected using consecutive sampling technique. Data analysis was performed using t-test, Chi-square, and logistic regression with a significance level of p < 0.05. There were significant differences in placental profiles between the case and control groups, where the HDK group had lower weight (420 ± 55 vs 510 ± 60 grams; p = 0.001), diameter (16.5 ± 1.8 vs 18.2 ± 1.5 cm; p = 0.002), and thickness (2.1 ± 0.4 vs 2.8 ± 0.5 cm; p = 0.001). The incidence of infarction (60.0 % vs 20.0%; p = 0.002) and calcification (66.7% vs 26.7%; p = 0.001) was higher in the HDK group. The condition of newborns in the HDK group showed a higher incidence of LBW ( 50.0 % vs. 20.0%; p = 0.015), APGAR <7 (40.0% vs. 16.7%; p = 0.032), and asphyxia (43.3% vs. 16.7%; p = 0.021). Analysis showed that low placental weight (OR=3.8 ; p = 0.008), infarction (OR=4.5; p = 0.004), and calcification (OR=3.9; p = 0.006) were significantly associated with the condition of newborns. Placental profiles in hypertensive pregnancies experienced significant changes and were closely associated with the condition of newborns.